IDENTIFICATION OF TOURISM POTENTIAL IN THE NEW STATE CAPITAL REGION (EAST KALIMANTAN) - Jimmy Muller Hasoloan Situmorang; Rosianna Sianipar; Juliana Juliana; Rudy Pramono; Nova Bernedeta Sitorus (SEAN Institute, 2023)
The candidate for the state capital is a new colour for Indonesia. Opinions from the public also varied, but the people of East Kalimantan should be proud of the election of their province, which is considered ideal to become the new national capital. The election of Kutai Kartanegara Regency and North Penajam Paser Regency has fulfilled the requirements as the new national capital based on the results of a 3-year study where the two areas have a minor disaster risk. Becoming the new national capital is an opportunity for East Kalimantan to improve and increase the quality of tourism objects. East Kalimantan has a variety of natural, artificial and cultural tourism destinations that are expected to be able to attract and fulfil tourists' interest in travel. The Ministry of Tourism has mapped East Kalimantan into three National Tourism Destinations (DPN), one of which is the city of Balikpapan. This research aims to examine the tourism potential and the profile, characteristics, interests and conditions of the tourist market in the new nation's capital. In conclusion, Kalimantan's national capital is a city with interesting potential and uniqueness. In terms of history, culture, economy, infrastructure and sustainability, this city has many assets that can be developed and utilized for the progress and welfare of society. By exploring its potential, the nation's capital city of Kalimantan can continue to grow and become a centre for increasingly advanced political, economic and cultural activities. By exploiting existing strengths, overcoming existing weaknesses, taking advantage of available opportunities, and dealing with threats that may arise, tourism at IKN Kalimantan can develop into a leading destination in Indonesia and provide significant economic benefits for the local community. Mentawir Village in East Kalimantan has an attractive tourism potential. Its natural beauty, cultural heritage, and unique culinary delights make this village a unique and exciting destination. Tourists can enjoy adventures in national parks, experience authentic cultural life, and enjoy delicious specialities. With the development of tourism infrastructure and the involvement of the local community, Mentawir Village is ready to welcome tourists and provide an unforgettable experience. In developing tourism in Mentawir Village, taking advantage of existing strengths and opportunities is essential while overcoming weaknesses and dealing with possible threats. By planning an effective strategy and considering relevant tourism theories, this village can increase tourism potential, attract tourists, and achieve success in sustainable tourism development.